Healthcare Analytics : Foundations and Frontiers. - Mullner, Ross M.; Rafalski, Edward M. ([Place of publication not identified] : Routledge, 2019)
This is a comprehensive, practical guide which looks at the advantages and limitations of new data analysis techniques being introduced across public health and administration services. The Affordable Care Act (ACT) and free market reforms in healthcare are generating a rapid change of pace. The "electronification" of medical records from paper to digital, which is required to meet the meaningful use standards set forth by the Act, is advancing what and how information can be analyzed. Coupled with the advent of more computing power and big data analytics and techniques, practitioners now more than ever need to stay on top of these trends. This book presents a comprehensive look at healthcare analytics from population data to geospatial analysis using current case studies and data analysis examples in health. This resource will appeal to undergraduate and graduate students in health administration and public health. It will benefit healthcare professionals and administrators in nursing and public health, as well as medical students who are interested in the future of data within healthcare.
Introduction Ross Mullner and Edward M. Rafalski Managerial Epidemiology Edward Rafalski Healthcare and Population Data: The Building Blocks Razvan Marinescu The Trend Towards Connected Data Architectures in Healthcare Greg Jordan Knowledge Management for Health Data Analytics Charisse Madlock-Brown, Ian M. Brooks and James Beem Comparative Effectiveness Research Ross Mullner Geospatial Analysis Pradeep S. B Podila Futuring Ross Mullner Conclusion Ross Mullner and Edward M. Rafalski
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Public Health; Medical informatics